1992
DOI: 10.1159/000139007
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of Purinergic, Cholinergic and Adrenergic Functions in Rabbit Corporal Cavernosal Tissue

Abstract: Erection involves cholinergic, adrenergic as well as non-cholinergic non-adrenergic nerves. Endothelial-derived relaxation factor plays an important role in mediating smooth muscle relaxation, which is crucial in initiating and maintaining erection. We previously showed that adenosine 5’-triphosphate (ATP) can induce significant relaxation in rabbit corporal cavernosal tissue. The present study presents effects of different neuron-transmitters and the role of endothelium in controlling the contractile/relaxant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 11 publications
4
51
1
Order By: Relevance
“…On the other hand, others found that, in rabbit CCSM tissue, ATP played an important role in smooth-muscle relaxation, but its actions were independent of the endothelium. 7 Our previous data supported an independent NO-related mechanism. 17 Nevertheless, ATP enhanced the effect of the NO pathway, but appears not to be involved in activation.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…On the other hand, others found that, in rabbit CCSM tissue, ATP played an important role in smooth-muscle relaxation, but its actions were independent of the endothelium. 7 Our previous data supported an independent NO-related mechanism. 17 Nevertheless, ATP enhanced the effect of the NO pathway, but appears not to be involved in activation.…”
Section: Discussionsupporting
confidence: 58%
“…6 Early studies in isolated corpus cavernosum smooth muscle Purinergic agonists augment nerve-mediated relaxation in HCC (CCSM) preparations demonstrated that ATP and other purines decreased both basal and phenylephrinestimulated tension. 7,8 Intracavernosal injection of ATP in dogs increased intracavernous pressures leading to penile erection. 9 Lee and coworkers 10 suggested that P2X receptors acted during the detumesence process.…”
Section: Introductionmentioning
confidence: 99%
“…ATP can induce significant relaxations of rabbit cavernosal tissue which was unaffected by removal of the endothelium [402]. ATP has a powerful relaxant effect on corporal smooth muscle at high tone or pre-stimulated tissue, but causes contractions at low tone [443].…”
Section: Penis and Penile Erectionmentioning
confidence: 99%
“…It is known that purinergic transmission is important for initiation and maintenance of penile erection (Tong et al, 1992). Due to its short half-life, adenosine has been used as an agent for the diagnosis of vasculogenic impotence (Kilic et al, 1994) without interfering with systemic blood pressure (Takahashi et al, 1992).…”
mentioning
confidence: 99%